What Comes Around, Goes Around: Effects of Unethical Pro-Organizational Behaviour on Time Theft - Wu, Zhennan; Deng, Jianwei; Yu, Qianqian; Deng, Wenhao; Gao, Yongchuang; Guo, Yuangeng (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2025)
In recent decades, China's rapid economic expansion has been accompanied by a rise in corporate ethical scandals, which have drawn increasing attention to unethical pro-organizational behaviour (UPB)—actions intended to benefit the organization but violating ethical norms. While often justified by employees as organizationally beneficial, UPB carries significant psychological and behavioural consequences. Using cognitive dissonance theory, we examine how UPB leads to time theft through the chain mediation of ego depletion and moral sensitivity, with managerial recognition serving as a key boundary condition. We collected data from 432 randomly selected retail employees through a structured questionnaire, including demographic data and measures of UPB, ego depletion, moral sensitivity, managerial recognition and time theft. Statistical analyses were performed using SPSS 27.0 for preliminary analyses (e.g., reliability, correlation) and MPLUS 8.3 for path analysis and hypothesis testing, including confirmatory factor analysis (CFA) and mediation analysis. The results show that UPB increases ego depletion and directly promotes time theft, while also reducing moral sensitivity indirectly through ego depletion. Ego depletion and moral sensitivity sequentially mediate the relationship between UPB and time theft. Importantly, managerial recognition moderates the mediation path by strengthening the positive relationship between ego depletion and time theft. These findings reveal not only the underlying psychological mechanism of UPB but also how organizational feedback can unintentionally reinforce deviant behaviour. We conclude that organizations should carefully evaluate recognition practices and implement ethics-oriented support systems to mitigate the hidden costs of UPB.